Persepsi Siswa Terhadap Senam Anak Indonesia Hebat Di SMP Negeri 1 Mepanga - Daning Winandi; Gunawan Gunawan; Hendra Iskandar; Andi Sultan Brilin Susandi Eka Wahyudi; Tri Murtono (Universitas Hamzanwadi, 2026)
Low levels of physical activity among junior high school students are a major concern because they lead to a decline in students’ physical fitness and health. The “Great Indonesian Children’s Gymnastics” program was introduced as an effort to increase physical activity and foster healthy lifestyle habits; however, students’ perceptions of this program have not been extensively studied. This study aims to determine students’ perceptions of the “Great Indonesian Children’s Gymnastics” program at Mepanga State Junior High School 1. The method used was quantitative descriptive research employing a survey technique. The study sample consisted of 100 students selected through simple random sampling. Data were collected using a questionnaire containing 35 valid and reliable statements (Cronbach’s Alpha = 0.872). Data analysis utilized descriptive statistics. The results showed that students’ perceptions fell into the high category with a mean score of 3.78. A total of 69.0% of students fell into the high category, 20.0% into the moderate category, and 11.0% into the very high category. The indicators of interest and the alignment of rhythm with movement received the highest scores (3.86), followed by ease of following the movements (3.72), and understanding of the program (3.66). In conclusion, students responded positively to the “Great Indonesian Children’s Gymnastics” program. Further research is recommended to examine the program’s effectiveness on students’ physical fitness and academic achievement.